Nematode distribution and damage to yam in Central and Eastern Uganda - Mudiope, J.; Speder, P.R.; Coyne, Danny L.; Maslen, R.N.; Adipala, E. (2007)
Yams (Dioscorea spp.) are food crops of growing significance in sub Saharan Africa. Unfortunately, nematodes are major pests to their production. A study was undertaken in major yam growing areas of Uganda to investigate the association of plant parasitic nematodes with damage symptoms. Nematodes were assessed from tubers, roots and surrounding soil for seven cultivars belonging to Dioscorea alata, D. bulbisiana, D.burkilliana and D. cayenensis at harvest. Pratylenchus sudanensis was found in the greatest density and was followed by Meloidogyne spp. Higher densities of both nematodes were observed in the tubers rather than roots. Although symptoms of cracking and galling were relatively low, P. sudanensis incidence was strongly associated with cracking and Meloidogyne spp. with galling. Pratylenchus sudanensis and Meloidogyne spp. incidence their associated damage were, however, negatively correlated, suggesting inter-species competition. Principal components analysis of data suggested that differences in susceptibility to P. sudanensis occur between yam cultivars and species.